PNAIC: um estudo sobre o aproveitamento dos alunos de 4° ano das atividades de alfabetização e letramento na Escola de Ensino Fundamental Santa Mônica - GOMES, Edicleia Rodrigues (2019)
The present study was aimed at describing the methodological parameters of the National Pact for Literacy in the Right Age (PNAIC) and didactic activities to work with 4th grade students at the Santa Mônica elementary school in the municipality of Breves-Pá. Emphasis is placed on the evidence of the research done regarding the learning achievement of these students, as well as showing the activities used during this process and the importance of the PNAIC in the training of teachers and the development of activities aimed at literacy and literacy of students. To achieve this, a bibliographical and field research was carried out. In order to base the discussions of this research, we use the propositions of Kleiman (2007), Souza (2014), Mendonça (2007), besides the teachers' reports, object of this research. The research results point out that the didactic activities analyzed are relevant because they highlight central categories in the discussion of this theme.